EFEKTIVITAS PENYALURAN BANTUAN LANGSUNG SEMENTARA MASYARAKAT BAGI RUMAH TANGGA SASARAN DI KECAMATAN TANON KABUPATEN SRAGEN TAHUN 2013 - Agus Sudiro; Mohammad Gamal Rindarjono; Sigit Santosa (GeoEco, 2015)
The objectives of this research are: (1) to investigate the dispersion of poor families in Tanon sub-district, Sragen regency in 2013; (2) to investigate the dispersion of targeted households receiving temporary direct cash assistance in Tanon sub-district, Sragen regency in 2013; (3) to investigate the effectiveness of temporary direct cash assistance distribution in Tanon sub-district, Sragen regency in 2013; (4) to investigate the benefit of temporary direct cash assistance for the targeted households in Tanon sub-district, Sragen regency in 2013; and (5) to arrange the learning materials of Geography on the basic competency of Analyzing the Dynamics and Problems of Population and Human Resources in Indonesia for Development. This research used the qualitative research method with spatial approach. Its population was all of the targeted households receiving temporary direct cash assistance in Tanon sub-district, Sragen regency. The samples of research were taken by using the proportional random sampling technique and the simple random sampling technique. They consisted of 100 targeted households. The data of research were gathered through field observation, in-depth interview, and documentation. The results of research are as follows: 1) Of 17,686 households in Tanon sub-district, Sragen regency, 7,793 are poor families. The largest number of poor families, namely: 830 is found in Bonagung village, and the smallest number, that is 279, is found in Suwatu village. 2) Of 7.793 of poor families, 5,588 are the recipients of the temporary direct cash assistance. 3) Through the consideration of 14 criteria of poverty, 37 targeted households are eligible to receive the temporary direct cash assistance, and through the calculation of calorie adequacy, 76 targeted households are eligible to get the temporary direct cash assistance. Thus, the distribution of the temporary direct cash assistance to its recipients in Tanon subdistrict, Sragen regency in 2013 is effective with the percentage of 76%. 4) Through the consideration of income, rice price, and life style variables, the targeted households can feel the benefit of the program. The level of benefit in term of income and rice-purchasing ability is 91%, and that of benefit in term of life is 89%. 5) The result of this research is a supporting one to the learning material in Geography for Grade XI, Semester I of the 2013 curriculum on the on the basic competency of Analyzing the Dynamics and Problems of Population and Human Resources in Indonesia for Development.Keywords: Poor families, targeted households, effectiveness of temporary direct cash assistance distribution, and benefit